2010
DOI: 10.2109/jcersj2.118.847
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and mechanical properties of high-dispersion-treated carbon nanofiber/alumina composites

Abstract: High-dispersion-treated carbon nanofibers (CNFs) were used to fabricate uniformly-dispersed CNFs-alumina composites with enhanced mechanical properties. The treatment was effective in obtaining dense and uniform composites. The composites containing 0.40.8 wt % CNFs were densified to a relative density of more than 99% by vacuum sintering and subsequent hot isostatic pressing, and those containing 1.62.5 wt % CNFs were densified to full density by plasma activated sintering. The maximum bending strength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…It was reported in our previous paper 32) that because the number of bendings per CNF could increase with a decrease in average alumina grain size and the resistance for bridging and/or pull-out of the CNFs could be increased with an increase in the number of bendings per CNF, the fracture toughness of the HDTCNFs/alumina composites increased with a decrease in average alumina grain size. Because of the similar reason, the fracture toughness of the AT05-CNFs/alumina composites increased with a decrease in average alumina grain sizes and that of the AT5-CNFs/alumina composites increased with a decrease in average alumina grain sizes in the range of 1.62.8¯m.…”
Section: Fracture Toughness Of Compositesmentioning
confidence: 64%
See 3 more Smart Citations
“…It was reported in our previous paper 32) that because the number of bendings per CNF could increase with a decrease in average alumina grain size and the resistance for bridging and/or pull-out of the CNFs could be increased with an increase in the number of bendings per CNF, the fracture toughness of the HDTCNFs/alumina composites increased with a decrease in average alumina grain size. Because of the similar reason, the fracture toughness of the AT05-CNFs/alumina composites increased with a decrease in average alumina grain sizes and that of the AT5-CNFs/alumina composites increased with a decrease in average alumina grain sizes in the range of 1.62.8¯m.…”
Section: Fracture Toughness Of Compositesmentioning
confidence: 64%
“…Fracture toughness of the 0.42.5 wt % HDT-CNFs/alumina composite increased rapidly with a decrease in average alumina grain size. 32) Similarly, fracture toughness of the 0.4 wt % AT05-CNFs/alumina composite increased with a decrease in average alumina grain size. However, fracture toughness of the 0.4 wt % AT1-and AT5-CNFs/alumina composites increased with a decrease in average alumina grain sizes, showed the maximum value at average alumina grain sizes of 1.3 and 1.6¯m, respectively, and decreased as the average alumina grain sizes decreased further.…”
Section: Fracture Toughness Of Compositesmentioning
confidence: 90%
See 2 more Smart Citations
“…With that aim in mind for alumina ceramics, we have combined the high-dispersion-treated carbon nanofibers (CNFs), which are a type of multi-walled CNTs, with alumina. 9) In the study, we found that the fracture toughness of the CNF/alumina composites increased with a decrease in the average alumina grain size of the composites, regardless of CNF content in the range of 0.42.5 wt %. 9) In these composites, CNFs were observed bending along alumina grain boundaries.…”
Section: Introductionmentioning
confidence: 78%